Promoting Digital Literacy: Strategic Approaches to Web Archiving Implementation in Indonesian Archival Institutions - Setyawan, Herman; Aisyah, Aisyah; Widayati, Erna; Samsiyah, Siti (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
This study investigates the challenges and strategies associated with implementing web archiving across various institutions in Indonesia, including Universitas Terbuka, Universitas Sumatera Utara, Universitas Mataram, Universitas Diponegoro, Institut Teknologi Sepuluh Nopember, and several regional archival and library offices. Employing a mixed-method approach, the research combines quantitative data from a survey of 235 archivists and information professionals with qualitative insights gathered through interviews with institutional representatives. The findings revealed a limited familiarity with the concept and practice of web archiving among respondents, which hinders both interest and institutional readiness to adopt such practices. Contributing factors include gaps in digital literacy, inadequate training, and lack of institutional policy frameworks. To address these issues, the study recommends systematic efforts to improve digital competencies through targeted training programs and awareness campaigns. Enhanced understanding of web archiving is crucial for ensuring the long-term preservation of digital information, particularly in an era marked by rapid technological change and increased reliance on web-based content. The research underscores the need for collaborative strategies and policy integration to foster a sustainable web archiving culture across academic and government institutions in Indonesia.